SARS-CoV-2 Spike-Derived Peptides Presented by HLA Molecules - Andrea T. Nguyen; Christopher Szeto; Dhilshan Jayasinghe; Christian A. Lobos; Hanim Halim; Demetra S. M. Chatzileontiadou; Emma J. Grant; Stephanie Gras (Biophysica, 2021)
The SARS-CoV-2 virus responsible for the COVID-19 pandemic has caused significant morbidity and mortality worldwide. With the remarkable advances in medical research, vaccines were developed to prime the human immune system and decrease disease severity. Despite these achievements, the fundamental basis of immunity to the SARS-CoV-2 virus is still largely undefined. Here, we solved the crystal structure of three spike-derived peptides presented by three different HLA molecules, and determined the stability of the overall peptide–HLA complexes formed. The peptide presentation of spike-derived peptides can influence the way in which CD8+ T cells can recognise infected cells, clear infection, and therefore, control the outcome of the disease.